Visualizing connections: University campus and social infrastructure. (September 2022) - Pavan, Luís H; Oliveira, Lucas F; Mangrich, Camila P; Harthmann, Gabriela; Kos, Jose R
As a social infrastructure, the material substrates of a campus intertwine with the sociabilities it supports. Intending to identify the integration potential between a Brazilian public university campus and its surrounding neighborhoods, we mapped the campus' social infrastructures and identified through diagrammatic studies its morphological dimensions. Internet routers distributed on the university campus provided georeferenced data of the human dynamics on campus. Counting user connections in groups of access points, we obtained the population density of the potential social infrastructure use. Afterward, associating Wi-Fi data and typological information, we traced itineraries that connect these infrastructures. The results encompass a systemic view that highlights the campus' potential to develop sociability within a complex service network. Furthermore, through new readings of the social infrastructures, we suggest alternative potential uses. These results highlight the hybrid methodologies that associate objective characteristics of the built environment with data-driven methodologies, such as Wi-Fi-generated datasets.